The design and application of an agricultural sustainability index using item response theory - Brian Beadle (Universitäts- und Landesbibliothek Sachsen-Anhalt, 2023)
Agricultural sustainability (AS) is a key component in the UN's Sustainable Development Goals. Despite wide use of the concept in both research and policy, there is still not a universally accepted method for its measurement. This research proposes using item response theory (IRT) to generate a farm-level AS index. The thesis is comprised of three scientific articles: The first article develops and tests the IRT model design, second applies the model to the sustainability of non-food crop production in the context of the bioeconomy, and the third looks into the sustainability of organic versus conventional farms. The key findings of the research are that (1) constructing an AS index with IRT may be a suitable alternative to existing methods, (2) farms producing a combination of non-food crops with food crops are more sustainable on average than those not producing non-food crops, and (3) organic farms are more sustainable on average than conventional farms. – – Landwirtschaftliche Nachhaltigkeit (agricultural sustainability; AS) ist eine Schlüsselkomponente der UN-Ziele für nachhaltige Entwicklung. Obwohl das Konzept sowohl in der Forschung als auch in der Politik weit verbreitet ist, gibt es noch immer keine allgemein anerkannte Methode zu seiner Messung. In dieser Forschungsarbeit wird vorgeschlagen, die Item-Response-Theorie (IRT) anzuwenden, um einen AS-Index auf Betriebsebene zu erstellen. Die Arbeit besteht aus drei wissenschaftlichen Artikeln: Der erste Artikel entwickelt und testet das Design des IRT-Modells, der zweite wendet das Modell auf die Nachhaltigkeit der Non-Food-Pflanzenproduktion im Kontext der Bioökonomie an, und der dritte untersucht die Nachhaltigkeit von ökologischen gegenüber konventionellen Betrieben. Die wichtigsten Ergebnisse der Forschung sind, dass (1) die Konstruktion eines AS-Indexes mit dem IRT eine geeignete Alternative zu bestehenden Methoden sein kann, (2) Betriebe, die eine Kombination von Nichtlebensmittelpflanzen mit Nahrungspflanzen produzieren, im Durchschnitt nachhaltiger sind als solche, die keine Nichtlebensmittelpflanzen produzieren, und (3) ökologische Betriebe im Durchschnitt nachhaltiger sind als konventionelle Betriebe.
urn:nbn:de:gbv:3:4-1981185920-1128178
Keywords: 330; sustainable agriculture; item response theory; non-food crops; bioeconomy; organic farming